Analysis of Slang Language Found in The Song Lyrics “Enema of The State” Album By BLINK-182 - Laksono, Riva Guntur; Meiga Ratih Tirtanawat; Chyntia Heru Woro Prastiwi (PT. Pustaka Cendekia Publisher, 2024)
This research includes a slang analysis of the lyrics of selected songs from Blink-182's